2009
DOI: 10.1073/pnas.0810687106
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae are required for protease-selective signaling by protease-activated receptor–1

Abstract: Protease-activated receptor-1 (PAR1) is a G-protein-coupled receptor uniquely activated by proteolysis. Thrombin, a coagulant protease, induces inflammatory responses and endothelial barrier permeability through the activation of PAR 1. Activated protein C (APC), an anti-coagulant protease, also activates PAR 1. However, unlike thrombin, APC elicits anti-inflammatory responses and protects against endothelial barrier dysfunction induced by thrombin. We found that thrombin and APC signaling were lost in PAR 1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
170
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(184 citation statements)
references
References 32 publications
12
170
1
Order By: Relevance
“…In addition, APC bound to EPCR on endothelial cells promotes anti-inflammatory and cytoprotective signaling through the activation of PAR1 (4). APC cytoprotective signaling also requires the compartmentalization of PAR1 and its coreceptor EPCR in cholesterol-enriched caveolar microdomains (5,6). A previous study further showed that the cytoprotective activity of a noncoagulant APC is critical for reducing mortality associated with sepsis in an experimental mouse model (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, APC bound to EPCR on endothelial cells promotes anti-inflammatory and cytoprotective signaling through the activation of PAR1 (4). APC cytoprotective signaling also requires the compartmentalization of PAR1 and its coreceptor EPCR in cholesterol-enriched caveolar microdomains (5,6). A previous study further showed that the cytoprotective activity of a noncoagulant APC is critical for reducing mortality associated with sepsis in an experimental mouse model (7).…”
mentioning
confidence: 99%
“…In cultured human endothelial cells, thrombin activation of PAR1 promotes coupling to G protein α subunits 12 and 13 (Gα 12/13 ) and Gα q ; activation of Ras homolog gene family, member A (RhoA) and other signaling effectors that cause disassembly of adherens junctions; reorganization of the actin cytoskeleton; and transient disruption of the endothelial barrier (9,10). Conversely, APC cleaves and activates PAR1, albeit less efficiently than thrombin, and induces endothelial barrier stabilization through selective activation of Ras-related C3 botulinum toxin substrate 1 (Rac1) signaling (5,11). Unlike thrombin, APC activation of PAR1 does not promote coupling to Gα 12/13 or Gα q signaling but instead appears to require G protein α inhibiting activity polypeptide (Gα i ) signaling for cytoprotection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…APC-activated EPCR and PAR1 localize to membrane regions enriched in caveolin and promote cytoprotective pathways, thus decreasing mortality in animal models of sepsis (8,10). Earlier studies have shown that APC and thrombin show different effects at the PAR1: thrombin does not engage a coreceptor, induces complete cleavage of PAR1, and promotes PAR1 internalization and degradation; APC engages the coreceptor EPCR, induces limited cleavage of PAR1, and does not promote receptor internalization and degradation (8,11). Furthermore, thrombin is more potent than APC and promotes internalization of APC-bound PAR1 (11,12).…”
mentioning
confidence: 99%
“…Earlier studies have shown that APC and thrombin show different effects at the PAR1: thrombin does not engage a coreceptor, induces complete cleavage of PAR1, and promotes PAR1 internalization and degradation; APC engages the coreceptor EPCR, induces limited cleavage of PAR1, and does not promote receptor internalization and degradation (8,11). Furthermore, thrombin is more potent than APC and promotes internalization of APC-bound PAR1 (11,12). Previously, Trejo and coworkers reported that thrombin and APC stimulated different small GTPases, namely RHOA (by thrombin) and RAC1 (by APC), and only APC-induced effects required caveolin (11).…”
mentioning
confidence: 99%